PENGARUH APLIKASI KAHOOT SEBAGAI MEDIA PEMBELAJARAN TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATERI GETARAN GELOMBANG Kahoot merupakan aplikasi media pembelajaran bersama di kelas dengan bantuan koneksi internet yang bersifat sederhana namun bisa menyena - Cut Rosi Dyanti; Hafnati Rahmatan; A Halim; Muhammad Syukri; Elisa Elisa (Jurnal Penelitian Pendidikan IPA, 2022)
Kahoot is a shared learning media application in the classroom with the help of an internet connection that is simple but can be fun for students in improving the learning outcomes of the digital generation. The instrument used is in the form of choice questions to measure learning outcomes. Learning outcomes were analyzed using independent sample t-test based on the acquisition of N-gain. Testing the hypothesis of an increase in learning outcomes has tcount = 5.194 > ttable= 2.048 with a two-sided significance value (Sig. 2-tailed) smaller than = 0.05, i.e. 0.000, meaning that there is a significant difference in student learning outcomes in the control and experimental classes, then on the learning outcomes Ha is accepted and Ho is rejected. The difference in learning outcomes is significant, indicating the influence of the Kahoot application as a learning medium on student learning outcomes. The results of data analysis showed that the increase in student learning outcomes in the experimental class using the Kahoot application increased more than the control class without using the Kahoot application